2010
DOI: 10.1021/ol101448e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Solvent Effects on Hydrogen Abstraction Reactions from Carbon by the Cumyloxyl Radical. The Role of Hydrogen Bonding

Abstract: A kinetic study of the H-atom abstraction reactions from 1,4-cyclohexadiene and triethylamine by the cumyloxyl radical has been carried out in different solvents. Negligible effects are observed with 1,4-cyclohexadiene, whereas with triethylamine a significant decrease in rate constant (k(H)) is observed on going from benzene to MeOH. A good correlation between log k(H) and the solvent hydrogen bond donor parameter alpha is observed, indicative of an H-bonding interaction between the amine lone pair and the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 36 publications
9
86
0
4
Order By: Relevance
“…More importantly, our study of the reaction of CumO • with 1,4-cyclohexadiene revealed a small increase in k H on going from MeCN, benzene, or chlorobenzene (for which k H = 6.6−6.9 × 10 7 M −1 s −1 ) to MeOH and t-BuOH (k H = 8.3 × 10 7 M −1 s −1 ), 29 with the rate constant increasing by a factor of ca. 3 when the reaction was performed in TFE solution (k H = 1.9 × 10 8 M −1 s −1 ).…”
Section: ■ Introductionmentioning
confidence: 75%
“…More importantly, our study of the reaction of CumO • with 1,4-cyclohexadiene revealed a small increase in k H on going from MeCN, benzene, or chlorobenzene (for which k H = 6.6−6.9 × 10 7 M −1 s −1 ) to MeOH and t-BuOH (k H = 8.3 × 10 7 M −1 s −1 ), 29 with the rate constant increasing by a factor of ca. 3 when the reaction was performed in TFE solution (k H = 1.9 × 10 8 M −1 s −1 ).…”
Section: ■ Introductionmentioning
confidence: 75%
“…[6] Taking compounds cyclohexane and 1,4-cyclohexadiene as reference,n osignificant effect on the k H values was observed when the reaction was studied in aprotic solvents (isooctane,b enzene,c hlorobenzene,a cetonitrile: k H = 1.1-1.2 10 6 and 6.6-6.9 10 7 m À1 s À1 for cyclohexane and 1,4cyclohexadiene,r espectively). [41][42][43] An increase in reactivity was,however, observed in protic solvents,with the highest k H values being measured for both substrates in the strong HBD solvent TFE (k H (TFE)/k H (MeCN) = 4.0 and 2.9 for cyclohexane and 1,4-cyclohexadiene,r espectively). This behavior was explained on the basis of hydrogen bonding of the solvent…”
Section: Hydrogen Bondingmentioning
confidence: 96%
“…Representative substrates,s uch as THF, [41] cyclohexanol (CyOH), [45] 2,2-dimethylpropanal (DMPA), [43] N,N-dimethylacetamide (DMA), [44] and triethylamine (TEA), [42,45] all undergo predominant or almost exclusive HATt oC umOC from the a-C À Hb onds (the formyl C À Hb ond with DMPA and the CÀHbonds a to the nitrogen center with DMA). The highest k H values were measured in isooctane and the lowest ones in TFE (Scheme 14), which leads to the following k H (isooctane)/k H (TFE) ratios:4.5, 7.9, 11, > 540, and > 2900, for THF,CyOH, DMPA, DMA, and TEA, respectively.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The reaction of CumO• with hydrocarbons occurs with very similar rate constants in a wide range of solvents, because neither the reactants nor the transition state is strongly solvated [69]. On the other hand, the reaction of CumO• with triethylamine in methanol is sixfold slower than in MeCN [69].…”
Section: Intermolecular Non-covalent Interactions Of the Substrate Wimentioning
confidence: 99%
“…On the other hand, the reaction of CumO• with triethylamine in methanol is sixfold slower than in MeCN [69]. The relevant rate constants for the reactions of Et 3 N with CumO• are collected in Table 20.4 [66,69]. The relevant rate constants for the reactions of Et 3 N with CumO• are collected in Table 20.4 [66,69].…”
Section: Intermolecular Non-covalent Interactions Of the Substrate Wimentioning
confidence: 99%